2007 IFIP International Conference on Network and Parallel Computing Workshops (NPC 2007) 2007
DOI: 10.1109/icnpcw.2007.4351481
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Analyser for Email Classification Based on Grey List Analysis

Abstract: In this paper we propose a new technique of email classification based on grey list (GL) analysis of user emails. This technique is based on the analysis of output emails of an integrated model which uses multiple classifiers of statistical learning algorithms [8]. The GL is a list of classifier/(s) output which is/are not considered as true positive (TP) and true negative (TN) but in the middle of them. Many works have been done to filter spam from legitimate emails using classification algorithm and substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…The spam filter architecture was originally designed and developed for a single SVM classifier as detailed in [3,4]. We extended this architecture to be used for an ensemble-based generic multi-classifier that processes the information in serial [5].…”
Section: Multi-classifier Ubiquitous Multi-core (Mum)mentioning
confidence: 99%
“…The spam filter architecture was originally designed and developed for a single SVM classifier as detailed in [3,4]. We extended this architecture to be used for an ensemble-based generic multi-classifier that processes the information in serial [5].…”
Section: Multi-classifier Ubiquitous Multi-core (Mum)mentioning
confidence: 99%
“…The spam filter architecture was originally designed and developed for a single SVM classifier as detailed in [15,14]. We extended this architecture to be used for an ensemble based generic multiclassifier that processes the information in serial [13].…”
Section: Multi-classifier Ubiquitous Multi-core (Mum)mentioning
confidence: 99%
“…While previous research in spam classification is primarily concerned with using a text based single classifier [15,14] to detect spam messages, we have developed a novel spam filter architecture using a multi-classifier approach [13].…”
Section: Introductionmentioning
confidence: 99%
“…Different phishing corpuses have been used in our experiments and an analyzation has been made with regards to data set construction, evaluation metrics and preliminary setup. It has been shown that the performance of ML algorithm varies from one another even for same corpora (Islam et al, 2009). Based on this idea, we have experimented the rescheduling of the ML algorithms among the tiers and found variation of result.…”
Section: Introductionmentioning
confidence: 97%
“…The Internet services are used daily by millions of people to communicate around the globe and are a mission-critical application for many businesses (Islam et al, 2009). However, phishing has become one of the biggest worldwide problems facing the Internet users today over the last decade (Phishing activity trends report, 2005).…”
Section: Introductionmentioning
confidence: 99%